Essentials of life-span development - Santrock, John W. (New York, NY McGraw-Hill LLC, 2022)
"Essentials of Life-Span Development, 7e" allows students to study whenever, wherever, and however they choose. Regardless of individual study habits, preparation, and approaches to the course, Essentials connects with students on a personal, individual basis and provides a road map for success in the course"--Provided by publisher.
Biological Beginnings -- Physical and Cognitive Development in Infancy -- Socioemotional Development in Infancy -- Physical and Cognitive Development in Early Childhood -- Socioemotional Development in Early Childhood -- Physical and Cognitive Development in Middle and Late Childhood -- Socioemotional Development in Middle and Late Childhood -- Physical and Cognitive Development in Adolescence -- Socioemotional Development in Adolescence -- Physical and Cognitive Development in Early Adulthood -- Socioemotional Development in Early Adulthood -- Physical and Cognitive Development in Middle Adulthood -- Socioemotional Development in Middle Adulthood -- Physical and Cognitive Development in Late Adulthood -- Socioemotional Development in Late Adulthood -- Death, Dying, Grieving.
International student edition--Cover.
Includes bibliographical references (pages R-1-R-80) and indexes.
Keywords: Developmental psychology